2017
DOI: 10.4038/cjs.v46i2.7427
|View full text |Cite
|
Sign up to set email alerts
|

Haematological and antioxidant enzyme response to Lead toxicity in male Wistar rats

Abstract: The study evaluated the haematological and some antioxidant enzymes response to lead toxicity in male Wistar rats. Twenty male Wistar rats were divided into four groups viz., A, B, C and D. Group A served as the control while groups B, C and D were treated with 200, 300 and 400 ppm of lead (Pb) as lead acetate, respectively. Doses were orally administered in divided doses by intubation to ensure that each rat had the specified doses, after which they have access to water and feed. At the end of two weeks of tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
12
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 22 publications
5
12
0
1
Order By: Relevance
“…Blood or blood constituents are the best indicators of internal exposure of an individual to lead. The result in table 1 shows an increase in the blood lead concentrations which was consistent with earlier findings of Moussa and Bashandy (2008), Okediran et al, (2017) who reported that absorbed lead following oral ingestion is carried via blood to soft tissues and 95 % of blood lead is transported in erythrocyte as lead diphosphate. Therefore, accumulation of lead in the body could lead to destructive impacts in haematic, gastrointestinal and renal system (Correia et al, 2000).…”
Section: Discussionsupporting
confidence: 90%
“…Blood or blood constituents are the best indicators of internal exposure of an individual to lead. The result in table 1 shows an increase in the blood lead concentrations which was consistent with earlier findings of Moussa and Bashandy (2008), Okediran et al, (2017) who reported that absorbed lead following oral ingestion is carried via blood to soft tissues and 95 % of blood lead is transported in erythrocyte as lead diphosphate. Therefore, accumulation of lead in the body could lead to destructive impacts in haematic, gastrointestinal and renal system (Correia et al, 2000).…”
Section: Discussionsupporting
confidence: 90%
“…Exposure to lead may alter antioxidant defense mechanism, which results in an imbalance Groups between radical-generating and radical-scavenging activities, and consequently, the formation of oxidation products. The finding of elevation in MDA concentration in lead exposed animals is consistent with the result obtained in previous studies (Aksu et al, 2012;Nisar et al, 2013;Wang et al, 2013;Okediran et al, 2017), verifying that exposure to lead causes an increase in MDA concentration. The significant increase in MDA concentration produced by exposure to lead suggests an increase in lipid peroxidation, which is an indicator to increased levels of free radicals in the serum and tissues of lead exposed rats.…”
Section: Discussionsupporting
confidence: 82%
“…Surprisingly, it has not been closely investigated. Some published studies have discovered that natural antioxidants have an important role in abating oxidative stress caused by lead in animals [12]. In the present study, we focused on the extract of okra pods as a natural antioxidant.…”
Section: Introductionmentioning
confidence: 98%